A Study on the Attention of Yoga and Its Development Based on Complex Network Theory - Li, Pengchao; Miao, Qinghong; Meng, Yuchi; Ning, Jie; Long, Jing; Huang, Junya (Frontiers in Physics, 2021)
Taking Baidu search index as the data source, this research collects yoga-related data in various provinces in China, analyzes the public’s attention to yoga on the Internet from the perspective of the complex network theory, so as to dig out characteristics of those who are interested in yoga as well as the temporal and spatial change of yoga attention from 2011 to 2020. Then, by transforming the time series into a network through the VG model and HVG model, the paper analyzes the network characteristics and predicts the popularity of yoga. Furthermore, the publicity of yoga and the public’s attention to it are analyzed, considering the policy, national education level, the influence of TV, mobile phone and other communication equipment, so as to help the market to provide corresponding products and services in a targeted manner and to promote the healthy development of the yoga industry.